Attribute Computations in the DPoPb Graph Transformation Engine - Tran, Hanh Nhi; Percebois, Christian; Abou Dib, Ali; Féraud, Louis; Soloviev, Sergei (Electronic Communications of the EASST, 2011)
One of the challenges of attributed graph rewriting systems concerns the implementation of attribute computations. Most of the existing systems adopt the standard algebraic approach where graphs are attributed using sigma-algebras. However, for the sake of efficiency considerations and convenient uses, these systems do not generally implement the whole attribute computations but rely on programs written in a host language. In previous works we introduced the Double Pushout Pullback (DPoPb) framework which integrates attributed graph rewriting and computation on attributes in a unified categorical approach. This paper discusses the DPoPb’s theoretical and practical advantages when using inductive types and lambda-calculus. We also present an implementation of the DPoPb system in the Haskell language which thoroughly covers the semantics of this graph rewriting system.